2021
DOI: 10.1002/ana.26128
|View full text |Cite|
|
Sign up to set email alerts
|

Gut Microbiome Signatures of Risk and Prodromal Markers of Parkinson Disease

Abstract: Objective Alterations of the gut microbiome in Parkinson disease (PD) have been repeatedly demonstrated. However, little is known about whether such alterations precede disease onset and how they relate to risk and prodromal markers of PD. We investigated associations of these features with gut microbiome composition. Methods Established risk and prodromal markers of PD as well as factors related to diet/lifestyle, bowel function, and medication were studied in relation to bacterial α‐/β‐diversity, enterotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 49 publications
3
41
2
Order By: Relevance
“…Although several studies have identified changes in relative abundance of certain bacteria, including Prevotellaceae, Bifidobacterium, Akkermansia and Lactobacillus, in patients with PD, results often vary given differences in study design and methodology, patient populations, and choice of controls 209 . While it remains unknown how specific taxa of gut bacteria could contribute to or trigger PD, several studies have shown associations between motor symptoms or disease progression as well as conditions associated with early, pre-motor stages of PD and the relative abundance of certain bacterial families within faecal samples from patients [210][211][212] . Furthermore, changes in gut bacterial composition have been associated with intestinal inflammation in PD 206,213 .…”
Section: Polymyalgia Rheumaticamentioning
confidence: 99%
“…Although several studies have identified changes in relative abundance of certain bacteria, including Prevotellaceae, Bifidobacterium, Akkermansia and Lactobacillus, in patients with PD, results often vary given differences in study design and methodology, patient populations, and choice of controls 209 . While it remains unknown how specific taxa of gut bacteria could contribute to or trigger PD, several studies have shown associations between motor symptoms or disease progression as well as conditions associated with early, pre-motor stages of PD and the relative abundance of certain bacterial families within faecal samples from patients [210][211][212] . Furthermore, changes in gut bacterial composition have been associated with intestinal inflammation in PD 206,213 .…”
Section: Polymyalgia Rheumaticamentioning
confidence: 99%
“…Exposure to environmental toxicants via ingestion may induce gut microbiome alterations that contribute to increased risk for chronic disease including idiopathic PD. Despite some variability in human population study data (Keshavarzian et al 2020), a gut microbiome signature appears to be present in most individuals with PD that includes the depletion in relative abundance of SCFA producing genera, such as Blautia , and increased relative abundance of Bifidobacteria, Akkermansia, Clostridium, and Lactobacillus (Heinzel et al 2021; E. M. Hill-Burns et al 2017; Toh et al 2022; Wallen et al 2020). Thus, a convincing explaination suggests that altered gut microbiota contribute to elevated GI and systemic inflammation that may drive neuroinflammatory changes and/or influence the aggregation and spread of α-synuclein along the gut-brain axis (Houser and Tansey 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome is thought to play a role, in at least a subset of PD patients, in both the initiation and progression of PD pathology and symptomology (Gorecki et al, 2019;Yang et al, 2019;Liu et al, 2020). Studies have shown a correlation between the increased occurrence of neurodegenerative diseases and conditions known to be associated with disrupted gut microbiota diversity such as insomnia, REM sleep behavior disorder (RBD), and constipation, with approximately 40-65% of RBD patients developing a neurodegenerative disorder within 10 years of RBD diagnosis (Postuma et al, 2009;Heinzel et al, 2021). Moreover, in a study of 172 RBD patients, 94% of those with associated comorbid neurodegenerative disease had a form of synucleinopathy (Boeve et al, 2013).…”
Section: Microbiota Composition and Metabolites Associated With Parkinson's Disease And Symptom Severitymentioning
confidence: 99%
“…Various studies over the past few decades have observed distinct differences in microbiota composition between individuals with and without PD, as well as between individuals with different PD phenotypes of symptomology (Heintz-Buschart et al, 2018;Heinzel et al, 2021). A recent study observed differences in the microbiota (elevated Akkermansia, Eggerthella, and Synergistetes; depleted Prevotella) between A53T transgenic monkeys with early-stage PD and control monkeys (Yan et al, 2021a).…”
Section: Microbiota Composition and Metabolites Associated With Parkinson's Disease And Symptom Severitymentioning
confidence: 99%